The Effectiveness Of Health Education Program Towards Enhancing Knowledge, Attitude And Practice On Pap Smear Uptake Among Sahabat Amanah Ikhtiar Malaysia In Alor Setar And Sungai Petani - Romli, Rodziah (2018)
Cervical cancer is among the most common cancer in women worldwide and the Pap smear test is the primary screening procedure used to detect abnormal cells that may develop into cancer. The objectives of this study were to determine and compared mean knowledge of cervical cancer and Pap smear test, the attitude about the test and the practice of Pap smear screening among participants. This is a control community trial that used simple random sampling method to recruit 210 women entrepreneurs of Sahabat Amanah Ikhtiar Malaysia (AIM) from Alor Setar and Sungai Petani branch. The Random Number Generator was used to randomly assign the branch as a study group and control group with 105 participants in each group. The study group received Health Education Program that consist of an educational talk regarding cervical cancer and Pap smear screening, a video of Pap smear screening procedure, a sharing experience by cervical cancer patients and an informative pamphlet. Two messages reminder through Short Message Service (SMS) also given to study group as reinforcements. Whereas, the control group only received educational talk that exactly the same as study group. As expected, there was a significant difference (P<0.001) of knowledge score on cervical cancer, knowledge score on Pap smear and attitude towards Pap smear screening within the same groups after the intervention. However, there was no significant difference (P>0.05) between study and control group. The mean difference of attitude score was higher in study group 7.69 [(10.31,5.09) , P<0.001] as compared to control group 4.50 [(6.19,2.82) , P<0.001] after health education program. The Pap smear practice among study group was also increased up to 20% (P<0.001) compared to 13% (P=0.003) in control group. There was an additional of 11% of Pap smear practice among study group after reinforcement through SMS. The additional educational program that been implemented to study group did not seem to have much influence on the knowledge score of participants as compared to control group. However, the video on procedure of Pap smear screening, sharing experience by patient of cervical cancer and SMS reinforcement had a positive influence on attitude and practice of study group towards Pap smear screening. In conclusion, the structured health educational program with phone reminder is an effective tool in increasing knowledge, attitude and practice of women entrepreneur regarding Pap smear screening as compared to a single educational talk only.